Utilization of dental care among adult populations: a scoping review of applied models - Ashkan Negintaji Zardak; Mostafa Amini-Rarani; Ibrahim Abdollahpour; Faezeh Eslamipour; Bahareh Tahani (BMC, 2023)
Abstract Background The timely and appropriate utilization of dental health care is essential to the prevention and accurate treatment of oral diseases. Therefore, it is crucial that managers, health professionals and healthcare providers be fully aware of the predictors encouraging the utilization of dental services and reduce social inequalities. In this scoping review, we aimed to analyze the published articles and reports to find out the factors associated with dental services utilization and the comprehensiveness of the applied models among general adult populations. Materials and methods This scoping study was based on the 5-steps of Arksey and O'Malley framework. Keywords were selected under two main concepts: determinants of dental care utilization and the concept of the applied models. Searches were conducted in some electronic databses including PubMed, Google Scholar and Scopus with variations, and a combination of the keywords under the two main afore-mentioned concepts. All the relevant articles reporting the utilization of dental care and its potential predictors among adult populations were chosen. No restrictions involving terms of study time, location or methodological aspects of oral health utilization were considered. Using tables and charts mapping, we tried to group the studies based on the year of their publication, geographic distribution, the range of included indices and the type of their measurement. Also, a directed content analysis method was used to investigate the comprehensiveness of the studies in regard to considering the determinant factors at different levels suggested by the Andesen model. Results Fifty-two articles were included in the analysis. Thirty-six (69%) had been published between 2016 and 2020. The United States had conducted the most research in this scope. About 30% of studies had mentioned all three domains of demographics, social structure and beliefs, simultaneously. To evaluate the enabling factors, in 84.61% and 59.61% of studies, the income levels and insurance feature were assessed, respectively. 57.69% of the retrieved studies considered the perceived need features and 38.46% referred to the evaluated ones. The dental services utilization, in terms of the last visit during the "past 12 months", was assessed more commonly. Only 11.54% of studies did evaluate the contextual characteristics and about 71.15% of articles were relatively comprehensive. Conclusion Overall, it seems that in most of the studies, not all of the determinant factors at different levels of the Andersen model have been considered. In order to discover the conceptual linkages and feedback loops of the model, it is essential to conduct more comprehensive research in the future.